Extracellular Vesicles from Plasma of Patients with Glioblastoma Promote Invasion of Glioblastoma Cells Even After Tumor Resection - Ekaterina N. Lyukmanova; Artem V. Kirichenko; Igor A. Medyanik; Konstantin S. Yashin; Mikhail P. Kirpichnikov; Maxim L. Bychkov (Biomedicines)
Background: Glioblastoma (GB) is a highly aggressive tumor, whose progression is mediated by secretion of extracellular vesicles (EVs), which can pass the brain–blood barrier and be found in the plasma. Here, we performed a comparative analysis of the effects of EVs from the plasma of healthy donors (hEVs) and GB patients before (bEVs) and after (aEVs) tumor surgical resection on invasion of normal astrocytes and GB cells. Methods: We performed the transwell invasion assay, analyzed MAP kinases activation by Western blotting, studied SNAI1/SNAI2 cellular localization by confocal microscopy, measured cadherins expression by flow cytometry, and analyzed secretion of cytokines, which regulate migration and inflammation, by immunoassay. Results: hEVs did not affect invasion of astrocytes and GB cells, there was down-regulated cadherins expression in astrocytes, while there was increased E- and N-cadherin expression in GB cells. hEVs increased the secretion of inflammation and adhesion regulators both in astrocytes and GB cells. bEVs enhanced the invasion of GB cells but not of astrocytes via MAP AKT, JNK1/2/3, and p38 kinases activation, stimulated the clasterization of SNAI1 in the GB cell nucleus, promoted an E/N cadherin switch, and caused the secretion of inflammation and adhesion regulators in astrocytes and GB cells. aEVs exhibited the most of pro-oncogenic effects of bEVs (stimulation of GB cell invasion, SNAI1 nuclear localization, JNK1/2/3 activation, E/N cadherin switch, and secretion of inflammation and adhesion regulators in astrocytes and GB cells). However, aEVs effects were less pronounced than those of bEVs. Conclusions: In our study, we revealed common and different effects of plasma-derived hEVs, aEVs, and bEVs. hEVs can stimulate some pro-oncogenic effects in GB cells. Being less tumorigenic then bEVs, aEVs are still able to promote invasion of GB cells, probably remaining after tumor resection.